Growth Suppression of Hamster Flank Glands by Topical Application of an Extract from "Kwao Keur" (Pueraria mirifica) - Waranucha, Neti; Thongruang, Charlee (Asian Health, Science and Technology Reports, 2005)
Hamster flank gland growth is androgenic dependent and a widely used model for the study of topically applied androgens and anti-androgens. A chloroform-methanol extract of "Kwao Keur" (Pueraria mirifica) was tested using this model. The extract was applied on one of the paired flank glands leaving other as a control. The results showed that the extract effectively suppressed flank gland growth. The local effect was also indicated by the different growth between treated site (-2.6 %) and untreated site (6.8 %). Acute dermal irritation test of the extract was also conducted according to the Test Guidelines (TG) No. 404 of OECD Guidelines for Testing of Chemicals. Very slight degree of erythema formation was observed in one out of three treated sites on the skin of rabbits. This skin reaction was fully recovered within 24 hours. Since the effect of the extract was localized with low skin irritation, it may be potentially useful for treatment of androgen-dependent skin disorders.